COMPETITIVENESS ANALYSIS OF INDONESIAN ESSENTIAL OIL AS AN EXPORT COMMODITY IN THE INTERNATIONAL MARKET USING REVEALED COMPARATIVE ADVANTAGE (RCA) METHOD - Amallia Ferhat; Mohammad Prasanto Bimantio; Putu Fajar Kartika Lestari (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The demand for Indonesian essential oils in the global market has trended quite well in the past decade. However, there has been no significant effort to increase the competitiveness of Indonesian essential oils in the global market. Seeing the increasing demand for Indonesian essential oils and the competition between the fierce producing countries, it shows that Indonesian essential oils have the potential to be developed, especially by looking at Indonesia's position which is in the 6th order as the world's essential oil exporter in the last ten years (2011-2020). The purpose of this study is to determine the competitive position of Indonesia's essential oil exports in the international market using a comparative advantage approach and competitive advantage with the five main export destination countries of Indonesian essential oils (United States, India, France, China, and Singapore) using the Revealed Comparative Advantage (RCA) analysis method, based on comparative advantage analysis, Indonesia's essential oil position commodities are said to be strongly competitive because Indonesia's essential oil commodities have a comparative advantage or RCA>1 value in all major export destination countries that are the object of research, with the highest competitiveness between Indonesia and France. This happens because of the trend of export value that decreases from year to year and the market is less dynamic. Indonesian essential oil commodities can be declared quite strongly competitive but development is still needed so that Indonesian essential oil commodity products are increasingly in demand in export destination countries so that export market share increases consistently from year to year and Indonesian essential oil commodities are increasingly competitive.